Conscious Breathing: a Powerful Tool for Physical & Neuropsychological Regulation. The role of Mobile Apps - Drigas, Athanasios; Mitsea, Eleni (Technium Social Sciences Journal, 2022)
Breathing, although unconscious and often overlooked, is a central aspect of our whole being and one of our most vital functions. This review paper aims at investigating the physiological as well as the neuropsychological benefits of breathing training techniques. In addition, we examine the effectiveness of mobile breathing applications in upgrading human health and wellness. Finally, we discuss the role of metacognition in breathing, as the only means people have to gain awareness of the profound powers of breath and take conscious control of their health.